Differentiated interactive teaching materials based on PowerPoint and HTML5 to improve third-grade students’ mathematical critical thinking skills (Diniyah: Jurnal Pendidikan Dasar, 2026)
Developing mathematical critical thinking in elementary education requires teaching materials that are interactive, differentiated, and responsive to students’ diverse learning needs. This study aimed to develop differentiated interactive teaching materials based on PowerPoint and HTML5 for third-grade mathematics learning and examine their validity, practicality, and effectiveness. The study employed a research and development design using the ADDIE model. Data were collected through expert validation sheets, teacher and student practicality questionnaires, classroom observation, and mathematical critical thinking tests administered before and after implementation. The product consisted of three differentiated learning pathways, 18 interactive activities, and 45 higher-order thinking questions. The results showed that the product achieved a very valid category with an overall expert validation score of 88.4%. The practicality test also indicated a very practical category, with an average score of 86.4% from teacher and student responses. Students’ mean score increased from 54.6 to 80.4, with 85.7% achieving mastery and an N-Gain of 0.67. These findings indicate that the developed product can support differentiated mathematics learning and promote students’ mathematical critical thinking. Keywords: differentiated teaching materials; elementary mathematics; HTML5; interactive learning media; mathematical critical thinking; PowerPoint